A Closed-Loop Digital–Physical Workflow for Patient-Specific Surgical Guides in Maxillofacial Reconstruction: A Clinical Feasibility Study - Emilia Smolarek; Filip Górski; Dominik Kłak; Magdalena Żukowska; Łukasz Słowik; Nikola Vitkovic; Rǎzvan Pǎcurar (Applied Sciences, 2026)
This study presents a closed-loop digital–physical workflow for manufacturing patient-specific anatomical models and surgical guides for maxillofacial reconstruction. The workflow combines medical-image segmentation, additive manufacturing of anatomical models, surgeon-led physical simulation, re-digitization of the modified models, landmark-based and surface-based alignment with the original CT-derived anatomy, with FFD used as a limited supporting approach for localized geometry updating, CAD design, and fabrication of sterilizable guides. Technical feasibility was examined in two detailed mandibular reconstruction cases involving temporomandibular joint prosthesis implantation. The workflow was subsequently used in adapted forms in eight clinically heterogeneous mandibular reconstruction cases related to oncological treatment. These cases are reported as supplementary clinical implementations and were neither treated as direct replications of the complete closed-loop methodology nor pooled for quantitative comparison. In the two detailed cases, the guides were verified on the anatomical models, used intraoperatively, and followed by postoperative imaging providing qualitative clinical confirmation of implant positioning. The study did not include a direct CT-based control workflow or standardized geometric deviation analysis. Therefore, operating-time and cost effects are reported as case-specific observations and an illustrative scenario rather than comparative evidence. The main contribution is the physical-to-digital feedback step, which allows surgeon-introduced modifications of a printed model to be transferred back to the digital geometry before final guide design. The results support the technical feasibility and adaptability of the workflow, while prospective quantitative validation remains necessary.